Nansen in the frozen world [electronic resource] : preceded by a biography of the great explorer and copious extracts from Nansen's "First crossing of Greenland," also an account by Eivind Astrup, of life among people near the pole, and his Journey across northern Greenland with Lieut. R.E. Perry, U.S.N. - Read, John E. (John Elliot), b. 1845.; Berens, S. L. (Chicago : Waverly Pub. Co., 1897)
At head of title: The "Fram" expedition. "Profusely illustrated." "Followed by a brief history of the principal earlier Arctic explorations . by John E. Read, assistant editor of the "Columbian Cyclopedia." Electronic reproduction. Mode of access: Internet. 44